Recovery of silver from photographic waste: electrolysis behavior - Mohd Ashraf, Che Mat (2010)
Photographic waste is one of the wastes produced by the paper and printing industries. Photographic waste usually contains metal ions mostly silver, sodium, potassium and iron. Since silver is photosensitivity material and its valuable increasing price, people tends to recover the silver from photographic waste to reuse it in paper and printing industries. A lot of research had been done to effectively recover the silver from photographic waste. This research is to investigate the ability of electrolysis process to recover the silver from photographic waste. In the process of electrolysis, or commonly known as electrolytic silver recovery, a direct current is passed through a silver-rich solution between a positive electrode (the anode) and a negative electrode (the cathode). During the process, an electron is transferred from the cathode to the positively charged silver, converting it to its metallic state, which adheres to the cathode. There are two parameters that have been focused on; the effects of current supply to the electrolysis process on the yield of silver and the effects of distance between two electrodes on the yield of silver. The results show that the electrolysis is able to recover silver from photographic waste. For the current supply variable, the best current supply for the electrolysis process is 40 mA and variable of distance between electrodes contribute minor effect to the process. Electrolysis process is one of the cheapest processes since it is able to recover silver from photographic waste.